Kompetensi Kepribadian Guru dalam Konsep Tazkiyatu An-Nafs - Nur Afif; Muhammad Nuralamsyah Putra B; Nurhadi Kastamin; Asrori Mukhtarom (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine the teacher's personality competence, the basic concepts of tazkiyatu an-nafs, and to understand how to shape the teacher's personality through tazkiyatu an-nafs. This study uses a type of library research or literature review by collecting data or scientific papers that aim to collect literary data. The results of the research in this study stated that the teacher's personality competence is one of the competencies that is very important and close to students. The point is how a teacher has a personality that will be digested and imitated by the number of students. When a teacher does not have good personality competence, then there is the possibility of having a bad view of students. It will be different from a teacher who has good personality competencies, it will also get a good view of the students. The basic concept of tazkiyatu an-nafs is closely related to the formation of obedient human beings, maintaining their relationship with Allah, harmony with others who are able to deliver themselves to be a whole person (insan kamil). Tazkiyatu an-nafs is defined as the process of purifying oneself or cleansing the soul to become a better human being. Forming teacher personality competence through tazkiyatu an-nafs with piety, patience, tawakkal, sincerity, gratitude, zuhud, polite/forgiving, and aware of responsibility. The creation of a good personality through the tazkiyatu an-nafs will form serious educators in organizing themselves to become good personalities. If a teacher's soul becomes pure and continues to have a noble character, then what is done is to keep that soul pure and moral starting through consistency within oneself. Tazkiyah is intended to help teachers live their profession as an educator or teacher in submitting to Allah swt. as insan kamil (perfect human) according to the objectives of Islamic education. The formation of relationships is based on the tazkiyatu an-nafs path through 3 (three) directions, namely vertical, horizontal, and individual. These 3 (three) paths are taken by humans themselves to communicate well with Allah swt. (vertically) through the way of worship, maintaining good relations with fellow humans (horizontally) through the path of noble character (akhlakul karimah), as well as to oneself (individually). Keywords: Personality Competencies, Teachers, Tazkiyatu an-Nafs